2019
DOI: 10.1016/j.jobcr.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetric reliability of frontal facial photographs with radiographs and anthropometric measurements

Abstract: To evaluate relationships between frontal cephalograms and photographic measurements of Indian population with anthropometric measurements and if frontal photographic analysis could be utilized with precision for orthodontic diagnosis. Material and methods: A cross-sectional ex vivo study was conducted on 300 subjects with age range of 18-25yrs. Standardized frontal cephalograms and photographs were obtained for all subjects and were analysed with Nemoceph 10.4.2 (Nemotec Dental Systems, Madrid, Spain) softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…It has been suggested that the disagreements found in the determination of facial types by cephalometric and photographic analysis are due to the fact that cephalometric studies evaluate bone tissues in profile views, while photographs evaluate soft tissues in frontal views ( 14 ). Moreover, some studies have evaluated the concordance between clinical and cephalometric diagnosis and reported different results ( 20 - 24 ). However, no study has used the Bjork-Jarabak polygon to compare concordance with the photographic method in the Latin American population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the disagreements found in the determination of facial types by cephalometric and photographic analysis are due to the fact that cephalometric studies evaluate bone tissues in profile views, while photographs evaluate soft tissues in frontal views ( 14 ). Moreover, some studies have evaluated the concordance between clinical and cephalometric diagnosis and reported different results ( 20 - 24 ). However, no study has used the Bjork-Jarabak polygon to compare concordance with the photographic method in the Latin American population.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Перспективним напрямком наукового пошуку є вивчення можливостей поєднання потенціалу 3D обстеження у поєднанні з рентгенологічними методами, прикладом чого є напрацювання, що доводять доцільність інтеграції 3D фотографічних та рентгеногра-фічних методів, які, на думку авторів, пропонує багатообіцяючі клінічні перспективи. [23] Не менш цікавими є і нові технічні рішення при виконанні фотограмметрії, наприклад -отримання дзеркального відображення об'єкта одночасно у декількох ракурсах, а, отже, останнім часом науковці звертають увагу на можливість отримання дзеркальних відображень об'єкта, які можна використовувати окремо або разом із фотографіями самого об'єкта. [24] Перспективними є спроби інтеграції фотограмметрії та класичних діагностичних методів, наприклад -мікроскопії.…”
unclassified